2001
DOI: 10.1046/j.1365-2923.2001.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of threats and violent acts by patients against training physicians

Abstract: These findings underscore a priority for developing programmes which effectively reduce threats and violence against trainees and which lessen the psychological sequelae of these incidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 20 publications
2
50
1
2
Order By: Relevance
“…The literature on threats in the workplace, specifically those witnessed by health professionals, is rich in detail about the context and nature of the threat, but rarely provides data on the subsequent behaviour of the threatener (Flannery et al 1995 ;Brown et al 1996 ;Coverdale et al 2001 ;Davies, 2001 ;McKenna et al 2003). This contrasts with threats of self-harm, where an extensive literature is available to guide the clinician in an evaluation of risk ; much of it deriving from studies of suicide in the general population rather than just patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on threats in the workplace, specifically those witnessed by health professionals, is rich in detail about the context and nature of the threat, but rarely provides data on the subsequent behaviour of the threatener (Flannery et al 1995 ;Brown et al 1996 ;Coverdale et al 2001 ;Davies, 2001 ;McKenna et al 2003). This contrasts with threats of self-harm, where an extensive literature is available to guide the clinician in an evaluation of risk ; much of it deriving from studies of suicide in the general population rather than just patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…1 The risk of experiencing aggression at work is even greater in psychiatry and psychiatric trainees are most at risk. 2 The definition of violent behaviour in the literature varies widely, reflecting the many ways in which violence may affect health workers. In this article we have classified violence into either physical or verbal aggression.…”
Section: Discussionmentioning
confidence: 99%
“…In Britain, most physicians who responded to a survey reported experiencing violence within the past 12 months, and further reported being exposed consistently to a variety of abusive situations [10]. Another study broke down the types of abuse that physicians experienced [11]. The results found that 67% of the respondents reported having been verbally threatened, 54% reported being physically intimidated, 41% stated that they had witnessed property being damaged, and 39% reported being physically assaulted.…”
Section: Introductionmentioning
confidence: 99%